Factors Affecting Attitudes Toward Homosexuals Among Undergraduate Students in Malaysia - Ee, Siu Kwin; Pua, Xinyi; Teh, Sin Ting (2016)
Homosexuals faced sexual prejudice and discrimination by the society due to their sexual orientation, especially in Malaysia where homosexuality is illegal. Therefore, this study aimed to examine the relationship between intrinsic religiosity, gender role belief and the attitudes toward homosexuals among heterosexual undergraduates in Malaysia. Quantitative, cross-sectional research design was used in this correlation study. Four hundred sixty undergraduate students were recruited through convenient sampling. Both online and paper and pencil survey method were used in data collection. Attitudes Toward Lesbians and Gay Men Scale Revised 5-Item version (ATLG-R), Duke University Religion Index (DUREL), and Liberal Feminist Attitude and Ideology Scale (LFAIS): Gender Role subscale were used to measure the variables in this study. Result of the study revealed that those who had higher score in intrinsic religiosity showed more prejudicial attitudes toward homosexuality while those who held more feminist gender role belief had more positive attitudes toward homosexuality. Moreover, findings also indicated that males held more unfavorable attitudes toward both gay men and lesbians as compared to females. Furthermore, results of multiple regression revealed that gender role belief is the strongest predictor for the attitudes toward homosexuals, followed by intrinsic religiosity. The findings of the study are important for future studies as well as being a source of reference in planning awareness campaign and public health discourse.